Genetic divergence studies in cluster bean (Cyamopsis tetragonoloba (L) Taub.) - Ramzeena A (Department of Vegetable Science,College of Horticulture, 2018)
Cluster bean (Cyamopsis tetragonoloba (L) Taub.) is a hardy drought tolerant crop in warm tropical and subtropical regions. In southern parts of India, the pods which are rich in vitamin A, vitamin C, iron and calcium are consumed as a vegetable. The guar gum extracted from the seeds of cluster bean is used in paper, textiles and pharmaceutical industries. Genetic divergence studies help to determine the degree of variability present in a germplasm and to identify suitable genotypes for crop improvement. Eventhough wide variability is present in cluster bean, limited work has been done to exploit genetic resources to identify genotypes for vegetable purpose. In this context, the present study was undertaken with the objectives of determining the variability and correlation between yield and yield components in cluster bean. Thirty accessions of cluster bean were collected from NBPGR, Jodhpur and evaluated for different morphological and quality characters. The experiment was conducted in the Department of Vegetable Science, College of Horticulture, Vellanikkara, during August – October 2017. Thirty accessions were catalogued based on NBPGR crop descriptor. The accessions exhibited branching and non- branching growth habits. Except four accessions, all others were branching types. The non-branching types were CT-9, CT- 15, CT-17 and CT-27. All accessions were having light purple flower except CT-8 which had white flower. Pods were dark green to light green in colour, without pubescence and glabrous. Seed colour varied from light pink and light grey to dark grey. Significant differences were observed among thirty accessions of cluster bean for all the characters studied. Genetic parameters like GCV, PCV, heritability, genetic advance and genetic gain were estimated to study extent of variability. The effectiveness of selection depends up on the magnitude of heritability of the trait. Characters like plant height, number of branches, number of pod clusters/plant, number of pods/cluster, number of pods/plant, pod length, pod girth, pod weight and pod yield/plant exhibited high GCV, PCV and heritability, indicating that these traits can be improved through selection. Pod yield/plant was positively correlated with number of branches, number of pod clusters/plant, number of pods/plant, days to first harvest, pod weight, number of harvests, iron, calcium, total carbohydrates, crude fibre and vitamin C. Path coefficient analysis of yield and component characters revealed that number of pods/plant had maximum direct positive effect on pod yield followed by days to first fruit set, pod weight, plant height, number of harvests, number of branches, crude fibre and total carbohydrates. Hence, direct selection of accessions based on these traits would be useful for improving pod yield/plant. The genotypes CT-16, CT-18, CT-20 and CT-21 were found promising. In the present study, CT-20, CT-3, CT-6, CT-10 & CT-12 were found having better sensory qualities. Mahalanobis D2 analysis grouped the thirty accessions to VIII clusters. Cluster IV had maximum number of accessions, (8) followed by cluster I (7) accessions. There were three accessions in Cluster II, V and VI. Cluster III, VII and VIII had two accessions each. Inter cluster distance was maximum between III and II. Hence, parents can be selected from cluster II and Cluster III for production of hybrids.